The The effect of indonesian local culture integrated students' environmental awareness on sdgs: pls-sem approach - Berti Yolida; Risma M. Sinaga; Dina Maulina; Supriyadi Supriyadi (Universitas Negeri Jakarta, 2023)
Various ways have been carried out in the world of education to raise environmental awareness for students, but the efforts so far have not had a significant impact on sustainable development. Students have not fully demonstrated awareness of the environment. Therefore, this research was conducted with the aim of measuring student environmental awareness (EA) which integrates Indonesian local culture towards the Sustainable Development Goals (SDGs). This research design uses survey research. The method used in this study is a quantitative method with purposive sampling technique with a sample of 362 Biology Education students spread throughout Indonesia. This research questionnaire uses a Likert scale of 1-5. Data collection used a questionnaire containing statements totaling 17 items. All indicators as exogenous variables except SDGs as endogenous variables. This study used Structural Equation Modeling (SEM) analysis through the SmartPLS application. The research results show that there is an influence between culturally integrated environmental awareness, awareness of responsibility, and finding solutions to environmental problems against the SDGs. However, the indicator of realizing its role in the environment has no effect on the SDGs, even though the simultaneous influence of all exogenous variables is in the moderate category on the SDGs. The conclusion from this study is that there is a positive influence between culturally integrated environmental awareness, student awareness of responsibility for the environment, and awareness in finding solutions to environmental problems towards the SDGs, but still needs to be improved. Strengthening Indonesian local culture rooted in local wisdom in growing environmental awareness is urgently needed to achieve sustainable development goals. The recommendation in this study is that the use of an active learning approach, for example STEAM, which can stimulate creative problem-solving skills for environmental problems, can be a solution in developing students' environmental awareness.